Mass Spectral Analysis of Solvent Extracts of Fenugreek Seeds - Kabilan, S.; Kayalvizhi, R.; Balasubramanian, S.; Ramalingan, C. (Asian Journal of Chemistry, 2010)
Fenu greek seeds were extracted using the solvents in the order of n-hexane, chloroform and methanol based on their polarity. Residues from each solvent extract was collected separately and purified by column chromatography after running TLC. They were subjected to gas–chromatography (EI) masss as well as FAB–mass sepectroscopy and analysed.